Simulation Bursting Effects To The Performance Vertical Axiz River Turbine Using Computational Fluid Dynamics - Aank Suseno; Ridho Hantoro; Gunawan Nugroho (Institut Teknologi Sepuluh Nopember, 2015)
Turbulent flow in the open channel, often exhibit a phenomenon bursting in expansion or inhibition case. This phenomenon disturbing to the flow at the turbine area. In this study, Research to analyze the occurrence of interference bursting in the river turbine area, done by simulating the river flow with a variety of depths ratio y/L, using vertical turbine NACA 0018 in a trapezoidal channel, with k-ԑ turbulence models in CFD. From the simulation results the smaller ratio of the depth y/L, the force of turbulence flow (bursting flow) at the turbine increases.